Tumor-associated macrophages remodeling EMT and predicting survival in colorectal carcinoma. (1st February 2018) - Li, Si; Xu, Fangying; Zhang, Jing; Wang, Lili; Zheng, Yang; Wu, Xuesong; Wang, Jing; Huang, Qiong; Lai, Maode
ABSTRACT: The immune contexture, a composition of the tumor microenvironment, plays multiple important roles in cancer stem cell (CSC) and epithelial–mesenchymal transition (EMT), and hence critically influences tumor initiation, progression and patient outcome. Tumor-associated macrophages (TAMs) are abundant in immune contexture, however their roles in CSC, EMT and prognosis of colorectal cancer (CRC) have not been elucidated. In 419 colorectal carcinomas, immune cell types (CD68 + macrophages, CD3 +, CD4 + or CD8 + T lymphocytes, CD20 + B lymphocytes), EMT markers (E-cadherin and Snail) as well as the stem cell marker (CD44v6) were detected in tumor center (TC) and tumor invasive front (TF) respectively by immunohistochemistry. Tumor buds, that represent EMT phenotype, were also counted. It was found CD68 + macrophages were the most infiltrating immune cells in CRC. By correlation analysis, more CD68 + TF macrophages were associated with more CD44v6 expression (p < 0.001), lower SnailTF expression (p = 0.08) and fewer tumor buds (p < 0.001). More CD68 + TF macrophages were significantly related to more CD3 + TF T lymphocytes (p = 0.002), CD8 + TF T lymphocytes (p < 0.001) and CD20 + TF B lymphocytes counts (p = 0.004). Strong CD68 + TF macrophages infiltration also predicted long term overall survival. CRC patients with more tumor buds had worse survival. However, strong CD68 + TF macrophages infiltration could reverse the unfavorable results since patients with more tumor buds but increasing CD68 + TF macrophages infiltration had the favorable outcome, similar to lower tumor buds groups. This study provided direct morphological evidence that tumor-associated macrophages in the invasive front play critical roles in fighting with the unfavorable results of tumor buds, thus resulting favorable outcomes for CRC patients.